2006
DOI: 10.1634/stemcells.2006-0598
|View full text |Cite
|
Sign up to set email alerts
|

Improved Human Embryonic Stem Cell Embryoid Body Homogeneity and Cardiomyocyte Differentiation from a Novel V-96 Plate Aggregation System Highlights Interline Variability

Abstract: Although all human ESC (hESC) lines have similar morphology, express key pluripotency markers, and can differentiate toward primitive germ layers in vitro, the lineagespecific developmental potential may vary between individual lines. In the current study, four hESC lines were cultured in the same feeder-free conditions to provide a standardized platform for interline analysis. A highthroughput, forced-aggregation system involving centrifugation of defined numbers of hESCs in V-96 plates (V-96FA) was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
274
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(284 citation statements)
references
References 36 publications
9
274
1
Order By: Relevance
“…This even distribution, combined with a reduction in debris and larger aggregates, translated to morphologically uniform EBs after 4 days of culture (Fig. S2 C-H), suggesting that PDMS surfaces may better support EB development (22)(23)(24).…”
Section: Pdms Surface Promotes Formation Of Intermediate-size Ebsmentioning
confidence: 93%
“…This even distribution, combined with a reduction in debris and larger aggregates, translated to morphologically uniform EBs after 4 days of culture (Fig. S2 C-H), suggesting that PDMS surfaces may better support EB development (22)(23)(24).…”
Section: Pdms Surface Promotes Formation Of Intermediate-size Ebsmentioning
confidence: 93%
“…First, hPSC-CMs are intrinsically heterogeneous, consisting of three subpopulations: atrial-, ventricular-, and nodal-like 10 . Furthermore, electrophysiology measurements have shown that the shapes of action potentials vary significantly between studies and within studies among different cell lines and differentiation methods 11,12 . Therefore, the high heterogeneity among hPSC-CMs requires that a large number of cells be analyzed to generate statistically meaningful conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers employ a myriad of aggregation methods for EB formation which promote natural aggregation or artificially force cell-cell interactions, such as rotary mass suspension (Abilez et al 2006;Niebruegge et al 2008) or microwell centrifugation (Burridge et al 2007;Moeller et al 2008), respectively. Many differences exist between methods regarding aggregation efficiency (Carpenedo et al 2007).…”
Section: Introductionmentioning
confidence: 99%